1992
DOI: 10.1002/jbm.820260704
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum vitronectin and fibronectin in adhesion of fibroblasts following seeding onto tissue culture polystyrene

Abstract: The suitability of polymeric biomaterials as surfaces for the attachment and growth of cells has often been investigated in tissue culture. In this study the contribution that adsorption of serum fibronectin (Fn) or vitronectin (Vn) make to the attachment and spreading of fibroblast cells during the first 90 min following seeding was determined for two modified tissue culture polystyrenes, as model biomaterial surfaces. The amount of serum Vn and Fn which adsorbed onto tissue culture grade polystyrene (TCP) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
133
2
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 31 publications
16
133
2
2
Order By: Relevance
“…The differential affinity model is supported by studies that showed large differences in the adsorption of fibronectin onto various surfaces (59)(60)(61)(62). In addition, the initial spreading of 3T3 cells on HEMA-EMA copolymers is linearly correlated with the amount of fibronectin adsorbed to the surfaces from serum (61).…”
Section: The Role Of Adsorbed Proteins In Cell Interactions With Solimentioning
confidence: 81%
See 1 more Smart Citation
“…The differential affinity model is supported by studies that showed large differences in the adsorption of fibronectin onto various surfaces (59)(60)(61)(62). In addition, the initial spreading of 3T3 cells on HEMA-EMA copolymers is linearly correlated with the amount of fibronectin adsorbed to the surfaces from serum (61).…”
Section: The Role Of Adsorbed Proteins In Cell Interactions With Solimentioning
confidence: 81%
“…Similarly, plasma deposited polymers which enhanced 3T3 and muscle myoblast cell growth also enhanced fibronectin adsorption from serum in comparison to untreated surfaces (63). Depletion studies, in which the fibronectin or vitronectin are selectively removed from the serum, have shown that vitronectin, rather than fibronectin, appears to be the primary adhesion factor for certain cells and surfaces (62,(64)(65)(66). However, the most recent studies of this type show that the enhanced affinity of fibronectin for the nitrogen rich Primaria tissue culture surface in comparison to ordinary oxygen rich tissue culture surfaces is sufficient to provide for the attachment of human vein endothelial cells to Primaria from serum depleted of vitronectin.…”
Section: The Role Of Adsorbed Proteins In Cell Interactions With Solimentioning
confidence: 99%
“…For example, recent studies linked mTOR to the signaling pathway of the ␣ V ␤ 3 integrin (64). ␣ V ␤ 3 integrin, a receptor for vitronectin, is the primary molecule required for attachment and spreading of fibroblasts on cell culture dishes (65). It is well documented that collagen message stability decreases after seeding fibroblasts in collagen matrices, whereas plating cells on plastic increases collagen synthesis (66).…”
Section: Discussionmentioning
confidence: 99%
“…integrins) are involved in the process of pattern recognition (Bershadsky et al, 2006). Immediately after contact of a substrate with cell culture medium, proteins (most importantly fibronectin and vitronectin in serum) start to adhere to the surface (Steele et al, 1992;Garcia and Boettiger, 1999). Specific binding sites in these proteins (the best known being the RGD peptide sequence) are recognized by integrin heterodimers on the cell membrane.…”
Section: Wwwecmjournalorg E Lamers Et Al the Influence Of Nanotopomentioning
confidence: 99%